Pelvic Floor Exercises Alone or in Combination with Perineal Electrical Stimulation for Uterine Prolapse: A Pilot Randomized Trial - Seveka Bali; Rashmi Bagga; Pradip Sarkar (Dr. Annil Mahajan, 2023)
Background: Pelvic floor rehabilitation is a non-invasive therapy crucial element of conservative treatment for uterine prolapse. Electrical stimulation is a novel type of pelvic rehabilitation that can enhance the results of pelvic floor exercises. Researchers have well documented its effectiveness in the treatment of urinary incontinence. Aims and Objective: The objective of the study was to see if combining perineal electrical stimulation with pelvic floor exercises provided additional advantages for uterine prolapse. Material and Methods: A total of twenty patients with uterine prolapse of grade one or two were randomly split into two equal groups. Group 1 received pelvic floor exercises and perineal stimulation for twelve weeks, whereas group 2 received pelvic floor exercises alone. Result: Perineal strength was evaluated using a perineometer, and the severity of prolapse symptoms and quality of life (QOL) using the pelvic organ prolapse symptom score questionnaire (POP-SS) on the 12th week following treatment completion. Perineal strength of group 1 was significantly higher to the group 2 [95% CI (0.04 to 12·15), p=0·04], indicating a relevant difference between groups, but there was no significant difference in POPSS score at 12 weeks in group 1 relative to group 2 [mean difference <1·01, 95% CI (-5.09 to 4.69), p=0·93]. Conclusion - Electrical stimulation in combination with pelvic exercises gave better results in terms of perineal strength. Moreover, both the groups improved their POP-SS scores with no significant difference between them.